Drought-tolerant rice, weather index insurance, and comprehensive risk management for smallholders: Evidence from a multiyear field experiment in India - Ward, Patrick S.; Makhija, Simrin; Spielman, David J. (International Food Policy Research Institute, 2017)
This paper provides some of the first empirical evidence on farmers’ demand for two drought risk–management products: a recently released DT rice cultivar and a more comprehensive DT-WII risk–management bundle. The paper makes several noteworthy contributions. First, drawing on insights from extreme value theory, it demonstrates how a comprehensive risk–management product could be designed, highlighting the reduction in the cost of drought insurance achieved through the bundling approach. Second, it estimates the price sensitivity of demand and other predictors of uptake for the DT cultivar and the DT-WII product by drawing on survey data from a two-year field experiment in which sales of the DT cultivar and DT-WII product were randomly assigned to villages across three drought-prone districts in Odisha. Finally, it explores the novel finding that uptake of the WII product persisted into year two at prices higher than the actuarially fair cost.